Sustainability practices for groundwater treatment to remove chloride and sulphate - Musa, Sabariah; Abdul Kadir, Muhamad Nazmie (Penerbit UTHM, 2020)
Groundwater is an alternative source of water for human consumption. Groundwater at RECESS, UTHM is one of the water sources that available to be used by UTHM resident. Unfortunately, it has a high content of chloride and sulphate concentrations in which originated from the mineral content in the ground. This chapter was conducted to review the effectiveness of the Nature Groundwater Eco-Treatment (N-GET) system that has been designed at RECESS in removing chloride and sulphate concentrations as well as pH and turbidity parameters. N-GET system is a natural treatment process without mixing any substances intended to improve the groundwater quality. This system uses two treatment tanks which are sedimentation tank, aeration tank and three sets of filters which were activated carbon filter, Do-It-Yourself (DIY) filter and ceramic filter. The chloride and sulphate parameters effectively removed by using a combination with aeration and sedimentation process and use any ceramic filtration in the market. It was performed more than 80 % than others by reducing all concentrations. Therefore, groundwater process by using any filters is the final stage and best practice to remove any concentrations safely.